Implementasi Algoritme 3DES pada Sistem Sharing Electronic Health Record (EHR) Berbasis Cloud - Haryadi Amran Darwito; Mike Yuliana; Reni Soelistijorini (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
Electronic Health Record (EHR) or medical history has been widely adopted to enable healthcare providers such as hospitals, insurance companies, and patients, to create, organize, and access EHR information from anywhere and at any time. From a health standpoint, to improve the quality of patient care, an EHR storage center is needed to ensure the EHR's novelty at all times. This underlies the need for an efficient, safe, and inexpensive mechanism for sharing EHR among health care providers. Cloud Computing has become a promising paradigm and gains more attention from academia and industry. This paradigm shifts the location of the computer infrastructure to third parties. Cloud computing not only increases the efficiency of storage and exchange of medical data but also allows accessing medical data from anywhere and anytime. In this paper, a mechanism of cloud-based sharing system equipped with the 3DES algorithm to secure health history data and the use of the smart card as a medium for controlling patient information access is proposed. The results of the tests indicate that the built system has fulfilled the security requirements such as privacy, authentication, confidentiality and integrity.